HISTOPATHOLOGICAL SPECTRUM OF ENDOMETRIAL BIOPSIES – A STUDY OF 378 CASES AT AFIP PAKISTAN - Ali, Syed Salman; Muhammad, Iqbal; Shaukat, Javeria; Afzal, Saeed; Hashmi, Shoaib Nayyar; Hamdani, Syed Naeem Raza; Ahmed, Rabia (Pakistan Armed Forces Medical Journal, 2020)
Objective: To analyze the histopathological spectrum of endometrial biopsies.Study Design: Descriptive case series.Place and Duration of Study: Armed Forces Institute of Pathology (AFIP), Rawalpindi from December 2013 to August 2015.Material and Methods: All cases of endometrial biopsies were retrieved from AFIP data base. Age and histopathological diagnosis was noted, irrespective of the clinical presentation of the patients. The data was analysed by using computer software program SPSS version 19. Descriptive statistics like mean ± SD, percentages and frequencies were calculated for age and histopathological diagnosis. The data collected for study was statistically analysed using chi-square test.Results: A total of 378 cases of endometrial biopsies were included in the study. The age at presentation ranged from 13 to 75 years with median age of 40.73 ± 9 years. A total of 73.5% of the cases (n=278) were from 4th to 5th decade of life. The most common histopathological diagnosis was secretory endometrium; present in 117 cases (31%) followed by proliferative endometrium; 78 cases (20.6%). Disordered proliferative endometrium, chronic endometritis and endometrium with hormone induced changes were observed in 62 (16.4%), 41 (10.8%) and 36 (9.5%) cases respectively. Atrophic endometrium was diagnosed in 8 cases (2.1%) and there were 3 cases (0.8%) of endometrial polyp. Among endometrial hyperplasia, 23 cases (6.1%) were of simple cystic hyperplasia, 5 cases (1.3%) were complex hyperplasia without atypia and 4 cases (1.1%) were complex hyperplasia with atypia. Adenocarcinoma in situ (ACIS) was reported in only one case (0.3%). Comparison with other studies revealed the results matching with some and differing with others. Association of age with histopathological pattern was statistically significant with p value